An Economic Assessment of Mushroom Grower’s in Haryana (Indian Journal of Extension Education, 2018)
Mushroom cultivation offers a highly efficient method of not only biodegradation and bioremediation of agro-industrial waste but also biotransformation into proteinaceous food that can sustain food security in the developing countries. The technology for the cultivation and handling of Calocybe indica (milky mushroom) was propagated in the selected villages of the Haryana state. The sample size constituted of 200 farmers which were trained intensively for period of three years (2015- 2017). In each selected village a mushroom centre were developed through which farmers were given hand holding support. For better adaptability of cultivation technology of C. indica, readymade spawned bags were distributed to compare the biomass yield obtained with the bags prepared by farmers using the conventional method. The fresh mushroom yield varied from 40 - 70 kg/ 100 kg dry substrate. As per the economics calculated it was found that a farmer can earn profit in the range of ` 33570-93570/annum. Farmers have been found to adopt this technology and some of them continuing this venture as a small side business. The identified constraints and suggestions pertaining to the C. indica crop were also described for further encouragement of mushroom farming in rural areas.